An Analysis of the Second Year Students’ Ability of SMAN 3 Sijunjung in Transferring Active Voice into Passive Voice in Simple Sentence - Niki Lesmana; Aryuliva Adnan (Universitas Negeri Padang, 2020)
This study aimed to describe the ability of second year students of SMAN 3 Sijunjung in transferring active voice into passive voice in simple sentences. This research was limited to students' ability to transfer active into passive voice in simple past tense and present tense. The research design was descriptive quantitative. The population of this research was the second grade students of SMAN 2 Sijunjung. The population was 96 students from 3 classes, XI IPA, XI IPS1 and XI IPS2. The sample was taken by cluster random sampling technique so that the number of sample obtained was 29 samples. The instrument used was a grammar test for 60 minutes. Based on this research, the ability of second year students of SMAN 3 Sijunjung to transfer active into passive voice was in the category B (good). While, there were some questions that students have not understood how to transfer. It can be seen that 13% of students transfer incorrectly based on the placement of subject, 15% of students transfer incorrectly based on inappropriate use of be, and 28% of students transfer incorrectly based on verb changes. So, the most difficult aspect in transferring active into passive voice based on verb changes. Students were expected to better understand how to transfer active to passive voice by not paying attention to forming sentences properly.